1999
DOI: 10.1136/vr.145.16.468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an injectable ivermectin/clorsulon combination against Fasciola hepatica in sheep

Abstract: INFECTIONS of Fasciola hepatica are of considerable economic importance in sheep and cattle (Urquhart and others, 1989). Ivermectin, an avermectin belonging to the macrocycic lactone class of compounds, is highly effective against a broad spectrum of endoparasites and ectoparasites of sheep (Benz and others 1989), but members of this class of compound do not have useful or significant activity against F hepatica (Shoop and others 1995). Clorsulon is a sulphonamide compound that has been reported to have poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The most commonly used anthelmintic is ivermectin alone or in combination with clorsulon (e.g., ivomec plus), which are effective against wide range of external and internal parasites. Previous studies concluded that use of ivermectin in combination with clorsulon is an effective flukicide (Rehbein and Visser, 1999;Elitok et al, 2006;Hutchinson et al, 2009). Some farmers drenching their animals with other types anthelmintic such as albendazole or triclabendazole.…”
Section: Associated Risk Factors With Bovine Fascioliasismentioning
confidence: 99%
“…The most commonly used anthelmintic is ivermectin alone or in combination with clorsulon (e.g., ivomec plus), which are effective against wide range of external and internal parasites. Previous studies concluded that use of ivermectin in combination with clorsulon is an effective flukicide (Rehbein and Visser, 1999;Elitok et al, 2006;Hutchinson et al, 2009). Some farmers drenching their animals with other types anthelmintic such as albendazole or triclabendazole.…”
Section: Associated Risk Factors With Bovine Fascioliasismentioning
confidence: 99%
“…It is also effective against Fasciola hepatica infections in the rat, the host species used in the present study (Schulman et al 1979(Schulman et al , 1982a. Although clorsulon itself is not active against nematode and arthropod parasites, it is marketed in combination with ivermectin (Ivomec Super, Ivomec-F) as a broad-spectrum wormer (Rehbein and Visser 1999;Ibarra-Velarde et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Lambs of adult fluke based on postmortem examinations (Rehbein and Visser 1999) or 98 per cent based on faecal egg counts (Corba and others 1996). The efficacy in the present study was lower (74 per cent).…”
mentioning
confidence: 99%